W.H. Auden : the critical heritage - Haffenden, John (Critical heritage series., 1997)
W.H. Auden (1907-1973). Born in Britain, later became a US citizen, hailed as a prophetic genius, brilliant satirist and lyricist. Writings include: Poems, The Orators, Look Stranger. Volume covers the period 1930-1977.